2020
DOI: 10.3390/molecules25071672
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anthraquinone Compounds Inhibit Colon Cancer Cell Proliferation via the Reactive Oxygen Species/JNK Pathway

Abstract: A series of amide anthraquinone derivatives, an important component of some traditional Chinese medicines, were structurally modified and the resulting antitumor activities were evaluated. The compounds showed potent anti-proliferative activities against eight human cancer cell lines, with no noticeable cytotoxicity towards normal cells. Among the candidate compounds, 1-nitro-2-acyl anthraquinone-leucine (8a) showed the greatest inhibition of HCT116 cell activity with an IC50 of 17.80 μg/mL. In addition, a cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Cell death can occur through three routes: autophagy, necrosis, and apoptosis. Apoptosis is an intrinsic cellular suicidal mechanism, which is regulated by a complex network of signaling pathways, such as Caspase, Bax, Bcl-xL, and PARP pathway [ 41 , 42 , 43 , 44 ]. To further investigate the photoprotective mechanism of fucoidan, the apoptotic bodies and the expression of apoptosis-related proteins in UVB-irradiated HaCaT cells were measured.…”
Section: Resultsmentioning
confidence: 99%
“…Cell death can occur through three routes: autophagy, necrosis, and apoptosis. Apoptosis is an intrinsic cellular suicidal mechanism, which is regulated by a complex network of signaling pathways, such as Caspase, Bax, Bcl-xL, and PARP pathway [ 41 , 42 , 43 , 44 ]. To further investigate the photoprotective mechanism of fucoidan, the apoptotic bodies and the expression of apoptosis-related proteins in UVB-irradiated HaCaT cells were measured.…”
Section: Resultsmentioning
confidence: 99%
“…117 Perry et al synthesized a series of 1,4-and 2,6-di functionalized amido anthracene-9,10-diones and examined their cytotoxicity along with telomerase inhibitory activity. Among the synthesized, piperidine 2, 6-anthraquinone derivative (88) and N,N 0 -dimethiodide derivative (89) elicited good enzymatic inhibition of telomerase with IC 50 values of 4.5 and 9.4 mM, respectively. 118 Huang et al reported the synthesis of 1,5-bisthioanthraquinones and 1,5-bisacyloxyanthraquinones and examined their telomerase activity along with the expression of telomerase.…”
Section: Telomerase Inhibitorsmentioning
confidence: 99%
“…This reaction further sets off the e-cysteine protease pathway. 88 Comparative Molecular Field Analysis (CoMFA) and Comparative Molecular Similarity Index Analysis (CoMSIA) models were used to analyze the structure–activity relationship of the compounds. From the studies, it was interpreted that the activity of the compounds greatly depended on the electron-withdrawing capacity of the nitro group at the C-1 position; the higher the electron-withdrawing capacity, the more the inhibitory activity of the compound.…”
Section: Development Of Non-specific Cytotoxic Anthraquinone Derivativesmentioning
confidence: 99%
“…It prevented the generation of ROS, intracellular calcium ion levels, and phosphorylation of MAPKs in glutamate-mediated apoptosis [ 38 ]. Moreover, many studies have reported that anthraquinones, as antioxidants, have the potential to suppress oxidative stress within cells [ 43 , 44 , 45 , 46 ]. Thus, we focused on suppressing the oxidative potential of these anthraquinones in HDFs.…”
Section: Resultsmentioning
confidence: 99%